MDM2's dual mRNA binding domains co-ordinate its oncogenic and tumour suppressor activities. Issue 12 (26th May 2020) - Gnanasundram, Sivakumar Vadivel; Malbert-Colas, Laurence; Chen, Sa; Fusée, Leila; Daskalogianni, Chrysoula; Muller, Petr; Salomao, Norman; Fåhraeus, Robin
Abstract: Cell growth requires a high level of protein synthesis and oncogenic pathways stimulate cell proliferation and ribosome biogenesis. Less is known about how cells respond to dysfunctional mRNA translation and how this feeds back into growth regulatory pathways. The Epstein-Barr virus (EBV)-encoded EBNA1 causes mRNA translation stress in cis that activates PI3Kδ. This leads to the stabilization of MDM2, induces MDM2's binding to the E2F1 mRNA and promotes E2F1 translation. The MDM2 serine 166 regulates the interaction with the E2F1 mRNA and deletion of MDM2 C-terminal RING domain results in a constitutive E2F1 mRNA binding. Phosphorylation on serine 395 following DNA damage instead regulates p53 mRNA binding to its RING domain and prevents the E2F1 mRNA interaction. The p14Arf tumour suppressor binds MDM2 and in addition to preventing degradation of the p53 protein it also prevents the E2F1 mRNA interaction. The data illustrate how two MDM2 domains selectively bind specific mRNAs in response to cellular conditions to promote, or suppress, cell growth and how p14Arf coordinates MDM2's activity towards p53 and E2F1. The data also show how EBV via EBNA1 -induced mRNA translation stress targets the E2F1 and the MDM2 - p53 pathway.